Preparation of Al-Mg Alloy Electrodes by Using Powder Metallurgy and Their Application for Hydrogen Production - Wen-Nong Hsu; Teng-Shih Shih; Ming-Yuan Lin (Advances in Materials Science and Engineering)
The choice of an electrode is the most critical parameter for water electrolysis. In this study, powder metallurgy is used to prepare aluminum-magnesium (Al-Mg) alloy electrodes. In addition to pure Mg and Al electrodes, five Al-Mg alloy electrodes composed of Al-Mg (10 wt%), Al-Mg (25 wt%), Al-Mg (50 wt%), and Al-Mg (75 wt%) were prepared. In water electrolysis experiments, the pure Al electrode exhibited optimal electrolytic efficiency. However, the Al-Mg (25 wt%) alloy was the most efficient when the anticorrosion effect and materials costs were considered. In this study, an ultrasonic field was applied to the electrolysis cell to improve its efficiency. The results revealed that the current increased by approximately 23.1% when placed in a 30 wt% KOH solution under the ultrasonic field. Electrochemical polarization impedance spectroscopy (EIS) was employed to evaluate the effect of the ultrasonic field on the reduction of polarization resistance. The results showed that the concentration impedance in the 30 wt% KOH electrolyte decreased markedly by 44%–51% Ω.